Closed-end fund premia and returns implications for financial market equilibrium - Pontiff, J (Journal of Financial Economics, 1995)
This paper examines the relation between closed-end fund premia and returns. Additional evidence is provided on Thompson's (1978) finding that fund premia are negatively correlated with future returns. Funds with 20% discounts have expected twelve-month returns that are 6% greater than nondiscounted funds. This correlation is attributed to premium mean-reversion, not to anticipated future portfolio performance. Economically motivated explanations do not account for this effect.